Association between Troponin I and Mortality in COVID-19 Patients: Meta-Analysis Study - Krisnawati, Hesthi; Dewi, Yulia Lanti Retno; Murti, Bhisma (Indonesian Journal of Medicine, 2021)
Background: COVID-19 is a new disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 became a pandemic disease that killed 4 million people for almost 2 years. COVID-19 patients with comorbidities or risk factors are more prone to have a worse prognosis, one of which is heart disease which can be checked through troponin I values. This study aimed to determine the relationship between troponin I levels and mortality in patients with COVID-19.Subjects and Method: This was a systematic review and meta-analysis by searching for articles from databases such as Science Direct, Springer, Google Scholar, and PubMed using the keywords: troponin I, cohort, fatality, cardiac biomarker, death, coronavirus, COVID-19 mortality, and COVID-19. Ten accredited articles published between 2019-2021 were included for meta-analysis. The subjects of this study were 10,499 COVID-19 patients. The intervention in this study was high troponin I levels, while the comparison was normal troponin I levels. The outcome of this study is mortality in COVID-19 patients. Data processing using Review Manager software version 5.3 for the relationship between troponin I levels and mortality in COVID-19 patients.Results: From a meta-analysis of 10 primary research articles in China, Spain, New York (United States), France, Turkey, and Philadelphia (United States) showed an association between high troponin I levels and an increased risk of mortality in COVID-19 patients (aOR= 3.07; 95% CI= 1.68 to 5.61; p<0.003).Conclusion: High troponin I levels increase the risk of mortality in COVID-19 patients.Keywords: troponin I, heart disease, mortality, COVID-19.Correspondence: Hesthi Krisnawati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: hesthikrisna86@gmail.com. Mobile: +6285278067840.Indonesian Journal of Medicine (2021), 06(03): 347-353https://doi.org/10.26911/theijmed.2021.06.03.12